Respostas
respondido por:
3
2 * (1 - x) + 1 = 3 * (x - 3) - 2x
2 - 2x + 1 = 3x - 9 - 2x
Organize (números e letra de um lado e só números do outro) e fique atento com o sinal.
- 2x - 3x + 2x = - 9 - 2 - 1
- 5x + 2x = - 12
- 3x = - 12 * (-1)
3x = 12
x = 12 / 3
x = 4
2 - 2x + 1 = 3x - 9 - 2x
Organize (números e letra de um lado e só números do outro) e fique atento com o sinal.
- 2x - 3x + 2x = - 9 - 2 - 1
- 5x + 2x = - 12
- 3x = - 12 * (-1)
3x = 12
x = 12 / 3
x = 4
Perguntas similares
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
10 anos atrás
10 anos atrás